Eksperimentasi Model Pembelajaran Quantum Learning dengan Peta Konsep Terhadap Hasil Belajar Siswa - Milhah Mufidah; Oki Pradana; Budi Sasomo (UNION : Jurnal Ilmiah Pendidikan Matematika, 2022)
This research aims to find the differences between quantum learning models with concept maps and conventional learning models on student learning outcomes and which models are more effective. This research used a quasi-experiment. The population are class VIII from MTs PSA An-Noor Karangasri Ngawi, with 48 students as corespondent, divided into two class groups, and the research used saturation sampling and mathematical learning outcome test instrument. Data analysis used a one-way ANOVA test and post hoc test ANOVA. The conclusions: 1) The difference in mathematical learning outcomes between quantum learning models with concept maps obtained of 71.3 and conventional learning models obtained of 60.2 with an F count of 4.0697 more than an F table which is 4,05 and 2) Quantum learning models with concept maps are more effectively used than conventional learning models in the learning process with F count of 4,112 more than F table which is 4,05.